Sequence variant on 8q24 confers susceptibility to urinary bladder cancer - KIEMENEY LA; THORLACIUS S; SULEM P; GELLER F; ABEN KKH; STACEY SN; GUDMUNDSSON J; JAKOBSDOTTIR M; BERGTHORSSON JT; SIGURDSSON A; BLONDAL T; WITJES JA; et al. (2008)
We conducted a genome-wide SNP association study on 1,803 urinary bladder cancer (UBC) cases and 34,336 controls from Iceland and The Netherlands and follow up studies in seven additional case-control groups (2,165 cases and 3,800 controls). The strongest association was observed with allele T of rs9642880 on chromosome 8q24, 30 kb upstream of MYC (allele-specific odds ratio (OR) = 1.22; P = 9.34 x 10(-12)). Approximately 20% of individuals of European ancestry are homozygous for rs9642880[T], and their estimated risk of developing UBC is 1.49 times that of noncarriers. No association was observed between UBC and the four 8q24 variants previously associated with prostate, colorectal and breast cancers, nor did rs9642880 associate with any of these three cancers. A weaker signal, but nonetheless of genome-wide significance, was captured by rs710521[A] located near TP63 on chromosome 3q28 (allele-specific OR = 1.19; P = 1. 15 x 10(-7)).